A comprehensive review of free-form surface milling– Advances over a decade. (February 2021) - Mali, Rahul A.; Gupta, T.V.K.; Ramkumar, J.
Highlights: A comprehensive review (based on 168 papers) of free-form milling is presented. The advances over a decade (2009–2020) are discussed in five sections. Experimental, analytical, tool-path and inspection based studies are covered. The literature is presented and compared concisely in tables and flowcharts. The prominent findings/observations and scope for future studies are highlighted. Abstract: The advent of CNC machines resulted in the reduction of machining complexity through efficient programming and increased productivity. The free-form surface milling (FFSM) process comprises several applications in the aerospace and automobile industries that mainly concerned with accuracy of the finished part. Numerous studies were attempted over the years to understand the mechanism involved in FFSM, which reported and facilitated the advances in the overall process. The complex surface milling still poses challenges with continuous change in the tool-workpiece contact that leads to vary an effective tool radius, along with the active cutting speed and cutting forces during machining. Accordingly, the material removal mechanism changes from shearing to plowing (plastic deformation), and vice-versa, which determines the tool wear and overall part quality. This paper presents a review of the research work (a total of 168 papers) published over the past decade considering five main domains in the FFSM process, which leads to enhance accuracy, machinability, productivity, and machining economy. The experimental investigations highlighted the input-output correlations, parametric influence on various machining responses, while analytical models underline the principles and mechanics involved in the process and useful in predicting/estimating the responses. The tool-path generation leads to an efficient tool-path that minimizes the machining time and cost, enhancing the part surface quality, and the surface reconstruction includes an accurate representation of the machined surface in the FFSM. Finally, the part inspection process is implemented for effectively measuring and comparing the accuracy of the machined components is reported. The inclusive knowledge of all five elements of the FFSM process would facilitate a clear understanding of the overall process and useful in developing research objectives and future perspectives.